2004
DOI: 10.1023/b:emas.0000031724.22352.af
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Application of Poultry Manure to Crude Oil Polluted Soils on Maize (Zea Mays) Growth and Soil Properties

Abstract: An investigation of the effects of application of poultry manure to crude oil polluted soils on the growth of maize and soil properties was carried out under natural conditions at the Ambrose Alli University, Ekpoma, Nigeria. Potted maize plants were treated to crude oil pollution at four different levels (0, 25, 50 and 75 mL) and amended with poultry manure at four rates of application (0, 50, 100 and 150 kg ha(-1)) two weeks after pollution. Results obtained showed that percent survival rate, plant height an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 6 publications
4
21
0
Order By: Relevance
“…Jobson et al (1974) and De Jong (1980) report on unfavourable carbon to nitrogen ratios in their investigations. Nitrogen addition with mineral fertilizers (Kirkpatrick et al, 2006) or organic soil improvers (Callaham et al, 2002;Ogboghodo et al, 2004b;Adedokun and Ataga, 2007) may enhance the development of microbiological processes in soil and thereby improve the C/N ratio (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…Jobson et al (1974) and De Jong (1980) report on unfavourable carbon to nitrogen ratios in their investigations. Nitrogen addition with mineral fertilizers (Kirkpatrick et al, 2006) or organic soil improvers (Callaham et al, 2002;Ogboghodo et al, 2004b;Adedokun and Ataga, 2007) may enhance the development of microbiological processes in soil and thereby improve the C/N ratio (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…Ogboghodo et al [8] stated that the addition of poultry manure to crude oil-polluted soil caused an increase in plant height from 20 to 149 cm as level of manure applied increased from 0 to 150 kg/ha and dry matter yield also increased from 27 to 58 g within 2 weeks of study, and proposed the adoption of poultry manure for the stimulation of hydrocarbon in the soil as a good technique of battling petroleum contamination in the natural environment. Another study by Okafor et al [9] has proven that poultry manure is rich in organic matter thus allows for the growth of a substantial amount of microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of cow dung augmentation to enhance the growth of Eleusine indica grown in crude oil polluted soil had been reported in our earlier studies . Amadi and Uebari (1992) and Ogboghodo et al (2004) reported that amending crude oil polluted soil with poultry dung improved soil fertility and the growth of maize in such soil. According to Pilon-Smits (2005), the ability of plants to grow quickly is one of the factors that favour phytoremediation.…”
Section: Introductionmentioning
confidence: 99%